A Chandra X-ray census of the interacting binaries in old open clusters – NGC 188. Issue 3 (29th August 2018) - Vats, Smriti; van den Berg, Maureen; Wijnands, Rudy
ABSTRACT: We present a new X-ray study of NGC 188, one of the oldest open clusters known in our Galaxy (7 Gyr). Our observation with the Chandra X-ray Observatory is aimed at uncovering the population of close interacting binaries in NGC 188. We detect 84 sources down to a luminosity of LX ≈ 4 × 10 29 erg s −1 (0.3–7 keV), of which 73 are within the half-mass radius rh . Of the 60 sources inside rh with more than 5 counts, we estimate that ∼38 are background sources. We detected 55 new sources, and confirmed 29 sources previously detected by ROSAT and/or XMM–Newton . A total of 13 sources detected are cluster members, and 7 of these are new detections: four active binaries, two blue straggler stars (BSSs), and, surprisingly, an apparently single cluster member on the main sequence (CX 33/WOCS 5639). One of the BSSs detected (CX 84/WOCS 5379) is intriguing as its X-ray luminosity cannot be explained by its currently understood configuration as a BSS/white-dwarf binary in an eccentric orbit of ∼120 d. Its X-ray detection, combined with reports of short-period optical variability, suggests the presence of a close binary, which would make this BSS system a hierarchical multiple. We also classify one source as a new cataclysmic-variable candidate; it is identified with a known short-period optical variable, whose membership to NGC 188 is unknown. We have compared the X-ray emissivity of NGC 188 with those of other old Galactic open clusters. Our findings confirm the earlier result that old open clusters have higher X-ray emissivities than other old stellar populations.